Fatty acid signatures as indicators of diet in great skuas stercorarius skua , Shetland - Käkelä, A.; Crane, J.; Votier, S.C.; Furness, R.W.; Käkelä, R. (Marine Ecology Progress Series, 2006)
Fatty acid signatures (FAS) were determined in plasma and adipose tissue of great skuas Stercorarius skua from Shetland in order to test the applicability of this biomarker in estimating diets of wild scavenging seabirds. The plasma FAS were compared with those of captive herring gulls Larus argentatus, which were fed typical Northeast Atlantic demersal and pelagic fish. The individual fatty acids that showed the largest proportional changes in FAS due to changes of dietary fish in herring gulls also varied the most in wild great skuas, suggesting a dietary origin of these changes in FAS. Thus, great skuas that had recently been feeding largely on a demersal or terrestrial diet were distinguished from individuals feeding mainly on a pelagic diet. Pronounced variation in the plasma FAS of great skuas suggests either very flexible feeding behaviour or individual dietary specialisation, which concurs with previous studies based on pellets. Individuals that regurgitated pellets consisting only of demersal fish, bird or rabbit showed larger values of a specific polyunsaturated fatty acid ratio (20:4n-6/18:3n-3+18:4n-3+20:5n-3) than birds whose pellets also contained remains of pelagic fish. Although pellet data showed a clear dominance of demersal fish in the summer diet of the great skua, the large proportions of long-chain monounsaturated fatty acids (e.g. 20:1n-9 and 22:1n-11) in adipose tissue of the great skua suggest that a considerable part of fat accumulated outside the breeding season comes from fatty pelagic fish